The potential biofortification role of Actinopolyspora sp. JTT-01 in enhancing the yield and tissue chemical composition of caraway plants - Ahmed M. Mahmoud; Mohamed S. Sheteiwy; Ali El-Keblawy; Zaid Ulhassan; Maha H. Khalaf; Hussein S. Mohamed; Mohammad K. Okla; Amal Mohamed AlGarawi; Ahmed M. El-Sawah; Enas S. Ahmed; Ahmed M. Reyad (BMC Plant Biology)
Abstract The need for improving plant production, nutritional value, and medicinal applications has become increasingly important due to the growing global population. The caraway (Carum carvi L) plant has been recognized for its broad range of nutritional and therapeutic uses. Consequently, this study aimed to increase caraway seeds’ nutritional and biological value. To achieve this, the Actinopolyspora sp. JTT-0 strain, isolated from the medicinal plant Tephrosia purpurea, was investigated for its potential biofortification role to enhance caraway yield and quality. Our results revealed significant improvements (p < 0.05) in various physical parameters, such as seed yield, pod length, and bulk density, in the treated seeds compared to the controls. Along with the yield increase, there were notable elevations in primary metabolites such as total sugars, proteins, and amino acids. Furthermore, secondary metabolites, including essential oils (EOs), alkaloids, steroids, phenols, and vitamins (e.g., tocopherol and ascorbic acid), also showed significant increases. Notably, the EO constituents showed varying levels of enhancements, with the highest increases in β-pinene (186.2%) and carvacrol (49.2%). Moreover, the treated seeds exhibited improved biological activity, as evidenced by their anti-oxidant (anti-lipid peroxidation and DPPH assays) and anti-microbial properties compared to the controls. The study reported a positive biofortification effect of the Actinopolyspora sp. JTT-01 strain on enhancing caraway seed’s quality and yield. However, additional field trials are needed to evaluate the commercial biofertilization capacity of this strain for caraway and other plants.